Self-efficacy, social support and oral health-related quality of life in patients with kidney transplantation and under hemodialysis - Bero Luke Vincent Ernst; Deborah Kreher; Daniel Patschan; Rainer Haak; Thomas Ebert; Jonathan de Fallois; Gerhard Schmalz (BMC Nephrology, 2024)
Abstract Background Aim of this questionnaire-based cross-sectional study was to compare self-efficacy, social support, oral hygiene-related self-efficacy (OHRSE) and oral health-related quality of life (OHRQoL) between patients under chronic hemodialysis (HD) and patients after kidney transplantation (KTx) as well as a healthy comparison group (HC). Methods Patients under HD were recruited during their routine outpatient dialysis therapy, KTx patients during their maintenance appointment and HC patients during their regular dental check-up in the dental clinic. General self-efficacy, the OHRSE, social support (F-SozU-K14) and the OHRQoL (OHIP-G5) were assessed by specific validated questionnaires. The survey was performed by one experienced dentist. Results 44 HD, 40 KTx and 45 HC patients were included, between which the age and gender distribution was comparable (p > 0.05). With a median of 1.5 [IQR: 0–3], HD patients showed higher OHIP-G5 than the participants in KTx group (p < 0.01). Similarly, a significant difference was found between KTx (0, [0–0.5]) and HC (0, [0–3]; p < 0.01). HD patients showed a lower sum score of OHRSE, tooth-brushing, interdental-cleaning and dental-visit self-efficacy than the HC (p < 0.01). Similarly, HD patients had a lower sum score of OHRSE, tooth-brushing and dental-visit self-efficacy than the KTx group (p < 0.01). Moreover, the KTx group had a lower interdental-cleaning self-efficacy (p < 0.01) and sum score (p = 0.02) than the HC. The sum score of the general self-efficacy was comparable between the three groups (p = 0.19). The F-SozU-K14 revealed higher values in KTx (65.40 ± 5.33) compared with HD (60.95 ± 9.28) and HC group (61.71 ± 9.24; p = 0.03). Only in the KTx group, a significant association between F-SozU-K14 and OHIP-G5 was revealed (p = 0.05). Conclusions Patients under HD show a reduced OHRSE compared to KTx and HC and a slightly reduced OHRQoL compared to KTx patients. While general self-efficacy was comparable between groups, social support of HD patients was lower than of KTx patients. The OHRSE and OHRQoL might receive increased attention in dental care of HD patients.